Circadian Clocks and the Interaction between Stress Axis and Adipose Function - Isa Kolbe; Rebecca Dumbell; Henrik Oster (International Journal of Endocrinology)
Many physiological processes and most endocrine functions show fluctuations over the course of the day. These so-called circadian rhythms are governed by an endogenous network of cellular clocks and serve as an adaptation to daily and, thus, predictable changes in the organism’s environment. Circadian clocks have been described in several tissues of the stress axis and in adipose cells where they regulate the rhythmic and stimulated release of stress hormones, such as glucocorticoids, and various adipokine factors. Recent work suggests that both adipose and stress axis clock systems reciprocally influence each other and adrenal-adipose rhythms may be key players in the development and therapy of metabolic disorders. In this review, we summarize our current understanding of adrenal and adipose tissue rhythms and clocks and how they might interact to regulate energy homoeostasis and stress responses under physiological conditions. Potential chronotherapeutic strategies for the treatment of metabolic and stress disorders are discussed.